Effect of Loading Speed on Direct and Indirect Tensile Strength of Rock and Concrete - Riyadh Mohammed Ali Hayder, Mohammed; Fahimifar, Ahmad; Al Khafaji, Hazim (International Journal of Engineering and Technology, 2018)
The trial work and numerical demonstrating were considered to examine the impacts of strain rate in the rigidity of rocks and cement in the research facility. Three trial of the exploratory work were considered, guide pressure test to get immediate elastic outcomes, Brazilian split test, and three-point flexural stacking test, to get roundabout ductile outcomes. While the numerical displaying utilizing limited component programming ABAQUS, to examined numerically the examples of 48 research facility tests. Immediate and roundabout rigidity tests, arranged two kinds of totals (0-6) mm and (0-12) mm for solid examples and shake tests (sedimentary and changeable) utilizing distinctive strain rates (10-2, 10-4, 10-5)s-1. The test and numerical outcomes demonstrated that strain rate articulated impacts on the elasticity of shake and cement and impacts are reliant upon the kind of shake and cement consolidated materials, and the broke surfaces of the considerable number of examples in all tests turned out to be more straightened with the expanding strain rate. The numerical and test results demonstrate a decent assention. The surmised (11%-18%) contrast between the tests results acquired through trial and numerical demonstrating might be ascribed to the disentanglement utilized in the numerical displaying.
Keywords: Direct and Indirect Tensile Strength; Marble; Mortar; Shotcrete; Strain rate; Travertine